FORMULATION AND EVALUATION OF OINTMENT CONTAINING SUNFLOWER WAX - AVISH D MARU; SWAROOP R LAHOTI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present work was to formulate and evaluate ointment using sunflower wax. Methods: In the present work, ointment formulations were prepared using sunflower wax by fusion technique. Sunflower wax base was compared with standard base for its pH, appearance, strength, spreadability, water number, and washability. Further, the optimized formulation was prepared with 2% salicylic acid and evaluated for its physicochemical parameters, compatibility study, drug content, in vitro drug diffusion, ex vivo permeability, and skin irritation test using rat skin. Results: All of the prepared formulations of ointments were evaluated for its physicochemical parameters and all the findings obtained were within the prescribed limit. As compared to the ointment prepared by prototype formulae as per USP and IP, the formulation F3 containing 97% white petrolatum and 3% of sunflower wax showed good viscosity, strength, and spreadability. Based on viscosity, strength, and spreadability, formulation F3 was chosen as an optimized formulation. Conclusion: The ointment consisting of white petroleum base 97% and 3% sunflower wax can be used for topical and systemic delivery of active ingredient salicylic acid. The results showed that sunflower wax can be used in ointment base as far as its pharmaceutical properties are concerned. It can effectively replace comparatively costlier available ointment bases.